Analysis of The Independent Curriculum Concept Through The Constructivist Philosophy of Education and The Philosophy of Ki Hadjar Dewantara - Idawati, Idawati; Fariza, Andi Arbaina Fariza; Witasari, Witasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This research aims to determine and analyze perceptions of the constructivist philosophy and Ki Hadjar Dewantara's philosophy in relation to the independent curriculum. This research uses a qualitative approach with a literature review or literature study method. Research data was collected from articles and books about the educational philosophy and philosophy of Ki Hadjar Dewantara. Data validation and analysis was carried out using document triangulation. The results of the research or findings show that the independent curriculum is based on educational philosophy views, namely the philosophical views of constructivism and the philosophy of Ki Hadjar Dewantara. The constructivist philosophy believes that constructivist learning is relevant to independent learning programs which can be viewed from learning methods that focus on learning that focuses on cognitive maturity and gives freedom to students to be able to explore and explore their learning experiences independently. Meanwhile, Ki Hadjar Dewantara's philosophy provides a different philosophical basis for how education is implemented and internalized optimally. The relationship or connection between Ki Hadjar Dewantara's educational concept and the independent curriculum is part of Tri Rahayu's educational philosophy. This educational concept focuses on the fun or happiness of students. In the independent curriculum, the concept of student-centered learning is implemented, and teachers act as motivators and facilitators. The flow of constructivist educational philosophy and the philosophy of Ki Hadjar Dewantara is very relevant to the dynamics of the independent curriculum, this is evident from every view and meaning implied therein.